2018
DOI: 10.1093/asj/sjy130
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Differentiated Adipose-Derived Stem Cells Improvement of Survival and Neovascularization in Fat Transplantation

Abstract: These results indicated that co-implantation of fat lipoaspirate with ASCs differentiated toward an endothelial phenotype improves both survival and neovascularization of the transplanted fat lipoaspirate, which might provide benefits and represents a promising strategy for clinical application in autologous fat transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…A key challenge in regenerative medicine is tissue minimal manipulation, and we hope that this study may open the door to possible optimization processes associated with fat grafting operative procedures [47].…”
Section: Discussionmentioning
confidence: 99%
“…A key challenge in regenerative medicine is tissue minimal manipulation, and we hope that this study may open the door to possible optimization processes associated with fat grafting operative procedures [47].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical settings of ASC showed auspicious therapies, showing immunotolerant properties and easy isolation. As autologous fat transplantation is restricted by low vascularization, fat absorption and fibrosis, co-transplantation of ASC-derived extracellular vesicles with fat tissue into a mouse model increased tissue volume retention due to vascularization enhancement and inflammatory response [164,165]. The paracrine products of ASCs, analyzed by loading them into a microencapsulation device, enhanced the angiogenic activity of endothelial cells and influenced macrophages secretion.…”
Section: Allograftmentioning
confidence: 99%
“…Increasing evidence suggests that ADSCs with other types of MSCs, are anatomically and functionally associated with vascular and perivascular habitats in various tissues. Harris et al confirmed that the co-implantation of fat lipoaspirate with ADSCs differentiated toward an endothelial phenotype observably improved both survival and neovascularization of the transplanted fat lipoaspirate 74 . An interesting study demonstrated that CD146 positive cells selected from a heterogeneous mixture of ADSCs expressed higher levels of the adipocyte markers adiponectin and leptin, and possessed more favorable angiogenic and adipogenic properties, which might provide significant benefits for reconstructive and tissue-engineering applications in fat transplantation 75 .…”
Section: Adscs Angiogenesismentioning
confidence: 92%